Mapping of Land and Water Structures in The Wogi Irrigation District, Jayawijaya Regency - Harmonis Rante; Bahtiar Bahtiar (CV. Publikasi Indonesia, 2026)
An irrigation area is a unit of land that receives water from a single irrigation network, consisting of the area to be irrigated and the main structure of the irrigation network. There are various types of irrigation, such as surface irrigation, swamp irrigation, and pump irrigation, which are used to support agriculture. The irrigation areas in Jayawijaya Regency are managed by local farmers, using a rudimentary irrigation system that relies on rivers and rainwater. Considering the potential of existing natural resources, the performance of Jayawijaya Regency's irrigation areas needs to be optimised to increase local rice production to meet the region's food needs and boost farmers' incomes. Geological conditions in an area are the result of changes in rocks due to plate tectonic processes. Plate tectonics is the relative movement between one plate and another. When the plates move, the distance between two locations on different plates gradually changes. Changes in the geological structure are indicated by the distribution of folds and faults around the movement of the plates. This is what happened in Jayawijaya Regency, where its position is on the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate, causing the distribution of rock types (lithology types or stratigraphic units, whether igneous, sedimentary, or metamorphic rocks) and stratigraphic relationships.